Pengaruh Lokasi, Price Diskon Dan Kepercayaan Terhadap Keputusan Pembelian Konsumen Di Puncak Departemen Store Bengkulu - Sania Sera; Sri Ekowati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of location, price discounts and trust on consumer purchasing decisions at the Puncak Bengkulu Department Store. This type of research is a type of quantitative descriptive research, the object of this research is the consumers of the Puncak Bengkulu Department Store which is precisely located on Jl. Lieutenant Suprapto, Kec. Ratu Samban, Bengkulu City, Bengkulu. The sampling method uses a non probability technique, namely accidental sampling. The number of respondents in this study were 150 people. Methods of data collection using a questionnaire. Data analysis techniques using Multiple Linear Regression Analysis Test, and Hypothesis Test, namely t test and f test.The results of this study can be concluded that the location variable has a positive effect on purchasing decisions, price discounts have a positive effect on purchasing decisions, trust has a positive effect on purchasing decisions, and location, price discounts and trust have a positive and significant effect on product purchasing decisions. Shop Puncak Bengkulu Department Store.